POTENTIAL ANTI-INSECT LIME EXTRACT OF MINT LEAF (Mentha piperita L.) AND EXTRACT SOKA FLOWER (Ixora paludosa L.) ON RED FIRE ANT (Solenopsis invicta) ACTIVITY - Anggraini Widya Ningsi Boham; Harry Maurits Sumampouw; Mercy Rampengan (Indonesian Biodiversity Journal, 2023)
The mint plant (Mentha piperita L.) is one of the many aromatic herbal plants that produce essential oil commonly known as peppermint oil. Meanwhile, the soka flower plant (Ixora paludosa L.) is an ornamental plant that fills the planting elements with fast growth and beautiful, vigorous plants. This study aimed to assess the effect of lime insecticides combined with mint leaf extract (Mentha piperita L.) and soka flower extract (Ixora Paludosa L.) on red fire ants (Solenopsis invicta). This study used four red fire ant samples (Solenopsis invicta), which were divided into five treatment groups: X1 (75% mint leaf extract and 25% soka flower extract); X2 (75% soka flower extract and 25% mint leaf extract); X3 (50% soka flower extract and 50% mint leaf extract); Negative control (lime base); and Positive control (branded lime). The sample size for this study was 80 red fire ants (Solenopsis invicta), with each control group consisting of four fire ants, and the experiment was repeated four times. The Kruskal-Wallis test was used to analyze the data, revealing significant differences between the treatment groups. Therefore, the researchers concluded that the administration of 50% mint leaf extract and 50% soka flower extract effectively disrupted the activity of red fire ants